Assessment of Mental State — Selected Measuring Tools in Neurogeriatrics - Monika Biercewicz; Wiesław Fidecki; Mariusz Wysokiński; Beata Haor; Mariola Głowacka; Kornelia Kędziora-Kornatowska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Complete Cerebral Assessment (CGA) involves the assessment of a neurological patient in four basic areas where performance capacity, physical health, mental health, as well social and environmental factors are taken into account. Specially prepared research tools (scales, questionnaires) can be used to assess individual CGA components, which significantly facilitate it and influence its credibility. In addition, they allow to verify changes in patient’s condition over time, in the category of improvement or deterioration, and also help in the exchange of quantitative (clinical) information between health care providers. Based on the literature, there have been discussed the most frequently applied scales used to assess the mental state of neurogeriatric patients. There have been presented data of metrics such as Mini-Mental State Examination (MMSE), Abbreviated Mental Test Score (AMTS), Clock Drawing Test (CDT), Geriatric Depression Scale (GDS), Hamilton Depression Rating Scale (HDRS), and Beck Depression Inventory (BDI). (JNNN 2017;6(3):130–133)